Can adipokine visfatin be a novel marker of pregnancy‐related disorders in women with obesity?. (27th March 2020) - Wnuk, Anna; Stangret, Aleksandra; Wątroba, Mateusz; Płatek, Anna E.; Skoda, Marta; Cendrowski, Krzysztof; Sawicki, Włodzimierz; Szukiewicz, Dariusz
Summary: Overweight and obesity have become a dangerous disease requiring multiple interventions, treatment and preventions. In women of reproductive age, obesity is one of the most common medical conditions. Among others, obese state is characterized by low‐grade systemic inflammation and enhanced oxidative stress. Increased maternal body mass index might amplify inflammation and reactive oxygen species production, which is associated with unfavourable clinical outcomes that affect both mother and child. Intrauterine growth retardation, preeclampsia, or gestational diabetes mellitus are examples of the hampered maternal and foetoplacental unit interactions. Visfatin is the obesity‐related adipokine produced mainly by the visceral adipose tissue. Visfatin affects glucose homeostasis, as well as the regulation of genes related to oxidative stress and inflammatory response. Here, we review visfatin interactions in pregnancy‐related disorders linked to obesity. We highlight the possible predictive and prognostic value of visfatin in diagnostic strategies on gravidas with obesity.